Pengaruh Diameter Hidrolik Terhadap Perpindahan Panas Kolektor Surya Belokan Tajam - Ahmad Syuhada; Ratna Sary; Zakirullah Zakirullah (Jurnal Teknik Mesin Unsyiah, 2019)
Rectangular crossings with sharp turns have complex three-dimensional structures because the flow separation is caused by sudden changes in direction of flow in sharp turns. This study aims to determine the effect of variations in the width of the sharp channel solar collectors with hydraulic diameter factors to increase the heat transfer rate in solar collectors. The size of the collector examined was 2440mm x 1220mm in the form of a rectangular cross-section. Solar collectors use iron and iron gram absorber with a thickness of 30mm, the thermometer is placed on each track, channel, absorbent and output temperatur of each solar collector. The results of the study can be concluded that the solar collector with the largest hydraulic diameter value of 223 cm will produce the highest output temperatur and the temperatur distribution at the collector can reach 91º C at 13.30. This is because the greater the value of the hydraulic diameter or cross-sectional area will increase the heat transfer rate.